2013
DOI: 10.1593/tlo.12400
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Analysis of RTK Inhibitor Efficacy and Identification of Its Novel Targets in Glioblastomas

Abstract: Treatment for glioblastoma consists of radiotherapy and temozolomide-based chemotherapy. However, virtually all patients recur, leading to a fatal outcome. Receptor tyrosine kinase (RTK)-targeted therapy has been the focus of attention in novel treatment options for these patients. Here, we compared the efficacy of imatinib, sunitinib, and cediranib in glioblastoma models. In the present work, the biologic effect of the drugs was screened by viability, cell cycle, apoptosis, migration, and invasion in vitro as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 52 publications
4
86
1
Order By: Relevance
“…Some authors have identified KIT gene amplification as an alternative mechanism for KIT upregulation in these tumors [18][19][20]. However, we did not find any case with KIT gene amplification using quantitative real-time PCR, a very sensitive and specific methodology, previously optimized by us and reported by our group and other groups [34,36,67,68]. We observed an association between KIT mutation and higher Clark staging, indicating that KIT could be associated with a more aggressive disease.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Some authors have identified KIT gene amplification as an alternative mechanism for KIT upregulation in these tumors [18][19][20]. However, we did not find any case with KIT gene amplification using quantitative real-time PCR, a very sensitive and specific methodology, previously optimized by us and reported by our group and other groups [34,36,67,68]. We observed an association between KIT mutation and higher Clark staging, indicating that KIT could be associated with a more aggressive disease.…”
Section: Discussioncontrasting
confidence: 40%
“…In all assays, appropriate positive and negative controls of 4q12 loci amplification were included [36]. These controls had also been previously assessed by other methodologies, such as array-CGH and CISH [34,36,37].…”
Section: Methodsmentioning
confidence: 99%
“…Such down-regulation of RTKs could be per se incompatible with the tumorigenic competence of GBM cells [45, 6567]. Consistently, drugs targeting several RTKs at the same time elicit efficient responses on a range of GBM cells [45, 50, 54]. Besides RTKs, we show a severe alteration also of MAPKs, STAT3, and p53 intracellular pathways, each of them being able to contribute to GBM tumorigenicity [68, 69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to differences in mechanisms of angiogenesis inhibition associated with sorafenib, regorafenib, and other multikinase inhibitors and endothelial cell proliferation inhibitors. Akin to VEGFR inhibitors, sorafenib and regorafenib are associated with potent VEGFR inhibition in biochemical assays (sorafenib: IC 50 ∼ 26–100 nM; regorafenib: IC 50 ∼ 13–46 nM)29,34 and exhibit significant angiogenesis inhibition in the in vivo CAM assay at 1–3 μM 35,36…”
Section: Discussionmentioning
confidence: 99%